Scenes from a writer's life - Bond, Ruskin (New Delhi ; New York, NY : Penguin Books, 1997)
Autobiographical reminiscences of author about his childhood and youth.
Keywords: Bond, Ruskin -- Childhood and youth; Authors, English -- 20th century -- Biography; British -- India -- Biography; India -- Social life and customs